The New Variants of Modified Weighted Mean Iterative Methods for Fredholm Integro-Differential Equations - Aruchunan, Elayaraja (Curtin University, 2016)
In this research, the Modified Weighted Mean iterative methods are developed and investigated for solving Integro-differential equations of Fredholm type. The developed methods are further investigated by implementing computational complexity-reduction techniques on three combination sets of Central Difference-Composite Closed Newton-Cotes dense systems. All new variants of proposed methods are presented with strong convergence theorems and proofs. The effectiveness and efficiency of the methods are investigated and validated with some existing methods, and via vigorous numerical analysis.